2013
DOI: 10.1088/0004-637x/776/2/92
|View full text |Cite
|
Sign up to set email alerts
|

Source Regions of the Interplanetary Magnetic Field and Variability in Heavy-Ion Elemental Composition in Gradual Solar Energetic Particle Events

Abstract: Gradual solar energetic particle (SEP) events are those in which ions are accelerated to their observed energies by interactions with a shock driven by a fast coronal mass ejection (CME). Previous studies have shown that much of the observed event-to-event variability can be understood in terms of shock speed and evolution in the shock-normal angle. However, an equally important factor, particularly for the elemental composition, is the origin of the suprathermal seed particles upon which the shock acts. To ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 96 publications
2
18
0
Order By: Relevance
“…Klein et al (2008) used PS+PFSS to connect L1 footpoints to open fields in active regions for seven simple SEP events. Ko et al (2013) similarly correlated SEP Fe/O abundances with the footpoint field strengths for 24 gradual SEP events. In various STA/STB SEP event comparisons with EUV waves, Nitta (2012), Park et al (2013Park et al ( , 2015, and Gómez-Herrero et al (2015) also followed this approach.…”
Section: Photospheric Sourcesmentioning
confidence: 60%
“…Klein et al (2008) used PS+PFSS to connect L1 footpoints to open fields in active regions for seven simple SEP events. Ko et al (2013) similarly correlated SEP Fe/O abundances with the footpoint field strengths for 24 gradual SEP events. In various STA/STB SEP event comparisons with EUV waves, Nitta (2012), Park et al (2013Park et al ( , 2015, and Gómez-Herrero et al (2015) also followed this approach.…”
Section: Photospheric Sourcesmentioning
confidence: 60%
“…The arrival of the second shock just before the end of the first ICME raised the question whether the eruption of the second CME had destroyed the magnetic configuration of the field lines during the trace back period, and whether information of the background IMF conditions on the solar surface was destroyed. From our analysis, however, we showed that the eruption of CME took place right after our trace back period, indicating that the source regions of the IMF determined by the velocity trace back technique would be valid [ Ko et al , ]. It is also to be noted that the active region AR 8210 remained south of the magnetic neutral line (MNL) during the whole trace back period, indicating no change in the IMF configuration.…”
Section: Discussionmentioning
confidence: 74%
“…The open field lines, which remained constantly to the north of the heliospheric current sheet both on 29 April and 1 May, clearly suggest no change in their polarity during the trace back period, from 29 April to 1 May. It is also known from observations that, depending on the hemisphere, the open magnetic field lines spiral either inward or outward, and the configuration changes, generally, either during periodic solar polar reversals occurring at the maximum of each solar cycle [ Janardhan et al , , , ] or due to the wake of CME eruption [ Ko et al , ]. However, the polarity reversal of solar cycle 23 occurred in CR1949, while our event was during CR1935.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Analysis of MESEP events on March (17)(18) CME1, and accelerated by the CME driven shock [14]. Another study [21] considered this event gradual based on their investigation of the source region of the IP magnetic field and variability in heavy ion elements composition in gradual SEP events . The CME2 associated with the X1.5 flare, on 18 March appears to be the solar source of shock wave observed on 20 March.…”
Section: Pos(icrc2015)084mentioning
confidence: 99%